(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the era of globalization, ecological issues are becoming increasingly serious. This research examines problems such as global climate change, resource scarcity, and the decline of biodiversity. Expected ecological forecasts and their threats and opportunities for humanity are analyzed. This article provides recommendations to aid in the development of sustainable development strategies and emphasizes the importance of global cooperation.